The two eIF4A helicases in Trypanosoma brucei are functionally distinct - Rafael Dhália; Nina Marinsek; Christian Robson de Souza Reis; Rami Katz; J.R.C. Muniz; Nancy Standart; Mark Carrington; Osvaldo P. de Melo Neto (2006)
Protozoan parasites belonging to the family Trypanosomatidae are characterized by an unusual pathway for the production of mRNAs via polycistronic transcription and trans -splicing of a 5′ capped mini-exon which is linked to the 3′ cleavage and polyadenylation of the upstream transcript. However, little is known of the mechanism of protein synthesis in these organisms, despite their importance as agents of a number of human diseases. Here we have investigated the role of two Trypanosoma brucei homologues of the translation initiation factor eIF4A (in the light of subsequent experiments these were named as Tb EIF4AI and Tb EIF4AIII). eIF4A, a DEAD-box RNA helicase, is a subunit of the translation initiation complex eIF4F which binds to the cap structure of eukaryotic mRNA and recruits the small ribosomal subunit. Tb EIF4AI is a very abundant predominantly cytoplasmic protein (over 1 × 10 5 molecules/cell) and depletion to ∼10% of normal levels through RNA interference dramatically reduces protein synthesis one cell cycle following double-stranded RNA induction and stops cell proliferation. In contrast, Tb EIF4AIII is a nuclear, moderately expressed protein (∼1–2 × 10 4 molecules/cell), and its depletion stops cellular proliferation after approximately four cell cycles. Ectopic expression of a dominant negative mutant of Tb EIF4AI, but not of Tb EIF4AIII, induced a slow growth phenotype in transfected cells. Overall, our results suggest that only Tb EIF4AI is involved in protein synthesis while the properties and sequence of Tb EIF4AIII indicate that it may be the orthologue of eIF4AIII, a component of the exon junction complex in mammalian cells.